EFEKTIVITAS PEMBELAJARAN DARING DI PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA MENGGUNAKAN APLIKASI MOODLE (ELEARNING FKIP UNPAS) - Rendy Triandy; Adi Rustandi; Dheni Harmaen; Aries Setia Nugraha (STKIP Subang, 2022)
This research was motivated by learning affected by the Covid-19 pandemic at the Indonesian Language and Literature Education Study Program (PBSI), Faculty of Teacher Training and Education (FKIP), Pasundan University (Unpas) Bandung using the Moodle application (e-learning FKIP Unpas). This study aims to determine the mechanism for implementing the online learning process carried out at PBSI FKIP Unpas, to determine student satisfaction in carrying out online learning using the Moodle application, and to identify the effectiveness of online learning implemented at PBSI FKIP Unpas. The research method used is descriptive research with a qualitative approach that focuses on ongoing events and the results will be analyzed. The results of this study, namely the online learning mechanism applied at PBSI FKIP Unpas, were compiled and implemented systematically, starting from student registration as course participants to the actual learning process. After analyzing the survey results, most of the students were satisfied with the online learning mechanism of PBSI FKIP Unpas. Respondents assessed that online learning using the Moodle application (e-learning FKIP Unpas) was very effective at 23%, effective at 54%, and less effective at (16%). However, there were a small number of students who rated it as ineffective, namely 7%, while those who rated it very ineffective were 0%. Based on this, online learning using the Moodle application (E-Learning FKIP Unpas), is effectively applied in the Indonesian Language and Literature Education Study Program FKIP Unpas.